Monitoring training load in youth soccer players: effects of a six-week preparatory training program and the associations between external and internal loads - Lechner, Sandra; Ammar, Achraf; Boukhris, Omar; Trabelsi, Khaled; M Glenn, Jordan; Schwarz, Jesper; Hammouda, Omar; Zmijewski, Piotr; Chtourou, Hamdi; Driss, Tarak; Hoekelmann, Anita (Biology of Sport, 2023)
Thisstudy examined the effects of a six-week preparatory training program on physical performance and physiological adaptations in junior soccer players. Additionally, we investigated whether a relationship existed between external and internal loads. Youth soccer players (aged 16 years old) from a youth football academy participated in six weeks of pre-conditioning training. Wireless Polar Team Pro and Polar heart rate sensors (H10) were used to monitor physical performance indicators (sprint and acceleration scores, covered distance, maximum and average speed and duration), physiological responses (maximum and average heart rate [HR] and R-R interval, time in HR zones 4+5, and heart rate variability [HRV]), and training load score. Additionally, muscle status and rating of perceived exertion (RPE) scores were measured using digital questionnaires. Significant increases were observed in the majority of physical performance indicators [i.e., sprints (p = 0.015, ES = 1.02), acceleration (p = 0.014, ES = 1), total distance (p = 0.02, ES = 0.87), as well as maximum speed (p = 0.02, ES = 0.87)]. A trend towards improvement was observed in the remaining performance indicators (i.e., distance/min and avg speed; ES = 0.6), training load (ES = 0.2), muscle status (ES = 0.3)), and all physiological responses parameters (ES = 0.1 to 0.6). Significant correlations were found between the majority of external load parameters (i.e., performance indicators) and objective (i.e., physiological responses) and subjective (i.e., RPE, muscle status) internal load parameters (p < 0.001). The highest number of moderate-large correlations were registered between performance indicators and time in HR zone 4+5 (0.58 < r < 0.82), training load (0.53 < r < 0.83), average HR (0.50 < r < 0.87), maximal HR (0.51 < r < 0.54) and average R-R interval (0.58 < r < 0.76). HR zone 4+5, average and maximal HR, average R-R interval, and training load score may help control training parameters and reduce the risk of under- or over-training in youth soccer players. However, these conclusions should be confirmed and replicated in future studies with more diverse subject populations.